Comparison of 70% alcohol and 2% glutaraldehyde effectiveness to the amount of bacterial colonies on the dental chair unit In Department of Oral and Maxillofacial Surgery Faculty of Dentistry University of Sumatera Utara - Hendry Rusdy; Darmayanti Siregar; Ahyar Riza; Indra B. Siregar; Novita M. Sari (DiscoverSys Inc., 2020)
Objective: Disinfection is an act to kill and eliminate all forms of microorganisms including spores with physical or chemical procedures. One of the goals of disinfection in the health sector is to prevent cross infection through microorganisms that are found in blood, saliva and dental plaque that can contaminate the work surface.Material and Methods: This is an experimental research with pretest-posttest design. This study was conducted on 10 dental chair unit and the number of bacterial colonies is observed before and after disinfection using 70% alcohol and 2% glutaraldehyde.Results: The results showed that the number of bacterial colonies experienced a statistically significant decrease after disinfection with 70% alcohol with mean value of 318.20±217.52 before and 11.20±17.29 after disinfection, while 2% glutaraldehyde decreased with mean value before 194.20±206.61 and after disinfection 2.20±2.28. Comparison of the difference in mean number of bacterial colonies between 70% alcohol group and 2% glutaraldehyde group did not show a significant difference (p = 0.412).Conclusion: Based on the results, it can be concluded that there is no significant difference in the number of bacterial colonies between 70% alcohol and 2% glutaraldehyde. From the results, it can be concluded that there was nothing better in the act of disinfection of dental chair units using 70% alcohol and 2% glutaraldehyde in reducing the number of bacteria.